2020
DOI: 10.2147/ijn.s244686
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Antibiofilm Activity and Mechanism of Nanosilver- and Nanozinc-Incorporated Mesoporous Calcium-Silicate Nanoparticles</p>

Abstract: Background: Mesoporous calcium-silicate nanoparticles (MCSNs) have good prospects in the medical field due to their great physicochemical characteristics, antibacterial activity and drug delivery capacity. This study was to analyze the antibiofilm activity and mechanisms of silver (Ag) and zinc (Zn) incorporated MCSNs (Ag/Zn-MCSNs) with different percentages of Ag and Zn. Methods: Ag/Zn(1:9, molar ratio)-MCSNs and Ag/Zn(9:1, molar ratio)-MCSNs were prepared and characterized. Endocytosis of nanoparticles by En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 38 publications
1
43
0
4
Order By: Relevance
“…Furthermore, different types of nanoparticles inhibit biofilm formation in various bacterial species. For example, in a study by Mohanta and co-workers, newly synthesized silver nanoparticles were reported to possess antibacterial and anti-biofilm activities against Pseudomonas aeruginosa, Escherichia coli, and Staphylococcus aureus [106]. Previous studies have also reported that mesoporous calciumsilicate nanoparticles possess antibacterial activity against Enterococcus faecalis biofilms in different degrees [107].…”
Section: Confocal Laser Scanning Microscopy (Clsm)mentioning
confidence: 99%
“…Furthermore, different types of nanoparticles inhibit biofilm formation in various bacterial species. For example, in a study by Mohanta and co-workers, newly synthesized silver nanoparticles were reported to possess antibacterial and anti-biofilm activities against Pseudomonas aeruginosa, Escherichia coli, and Staphylococcus aureus [106]. Previous studies have also reported that mesoporous calciumsilicate nanoparticles possess antibacterial activity against Enterococcus faecalis biofilms in different degrees [107].…”
Section: Confocal Laser Scanning Microscopy (Clsm)mentioning
confidence: 99%
“…Mesoporous calcium silicate nanoparticles combined with silver nanoparticles were able to inhibit the growth of both planktonic and biofilm forms of E. faecalis [ 209 , 210 ]. Studies have also suggested their applicability as novel root canal sealers due to their bioactive and osteogenic properties [ 211 214 ]. Other nanoparticles with sustained antibiofilm activity that have been explored as root canal sealers include quaternary ammonium polyethyleneimine [ 215 ] and quaternary ammonium methacrylate nanoparticles [ 216 ].…”
Section: Clinical Implications Of Root Canal Infectionsmentioning
confidence: 99%
“… 118 With the addition of AgNPs, mesoporous calcium silicate nanoparticles showed sustained release of Ag ions and inhibited E. faecalis colonization. 119 , 120 Other studies found the combination of AgNPs and nano-zinc with mesoporous calcium silicate nanoparticles exhibited good antibiofilm efficacy, minimal cytotoxicity, 121 sustained ion release, dentinal tubule infiltration and negligible changes to the mechanical properties of dentine. 122 The substantivity of these compounds may be attributed to the mesoporous structure which allows these compounds to carry antimicrobial nanoparticles and support their sustained release.…”
Section: Intracanal Medicamentsmentioning
confidence: 99%
“… 126 Apart from their potential use as intracanal disinfectants, several authors have also advocated the development of calcium silicate nanoparticles into novel root canal sealers due to the aforementioned benefits. 121 , 122 , 126 …”
Section: Intracanal Medicamentsmentioning
confidence: 99%